Microscopic Colitis in Patients with Diarrhea of Unknown Etiology: Diagnosis and Treatment - Jacobus Albertus (The Indonesian Society for Digestive Endoscopy, 2012)
Chronic diarrhea is a common reason for referral to a gastroenterologist. Microscopic colitis (MC) is fairly common cause of chronic non-bloody diarrhea. Microscopic colitis which was previously regarded rare, now has emerged as a common cause of chronic diarrhea. The condition is characterized clinically by chronic non bloody diarrhea, a macroscopically normal or near-normal colonic mucosa, but microscopic examination of mucosal biopsies reveals diagnostic histopathological changes. Microscopic colitis mainly includes two diseases, collagenous colitis (CC) and lymphocytic colitis (LC). In CC the most characteristic feature is thickening of the sub-epithelial collagen layer (SCL) beneath the basal membrane intra-epithelial lymphocyte (IEL) infiltration although not asprominent as in LC. The diagnosis of LC relies on a characteristic increase of IELs, which exceeds 20 IEL/100 surface epithelial cells compared with 5 IEL/100 surface epithelial cells in normal colonic mucosa. Randomized controlled trials (RCTs) assessing therapies for microscopic colitis have been performed. A previously published review showed that budesonide was effective in producing both clinical and histological responses in patients with collagenous colitis. This review will focus on epidemiology, clinical features and treatment of MC. Keywords: chronic diarrhea, microscopic colitis, lymphocytic and collagenous colitis